THE ANALYSIS OF INDONESIA'S IMPORTANT ROLE TO KEEP PEACE IN AFGHANISTAN USING A SYSTEM DYNAMIC CONCEPT APPROACH - Arief Rachman (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Peace in the Central Asia region is a very dynamic situation and changes rapidly from time to time based on the important role of each country in the region. Various conflicts of interest occur in Afghanistan, ranging from the internal conflict in Afghanistan itself and external conflicts involving many countries including the United States, Israel, Russia, and so on. Indonesia, as one of the countries with the largest number of Muslims, also has a major concern for peace in the Central Asia region, especially Afghanistan. This study aims to analyze Indonesia's role in achieving peace in the Central Asia Region, especially in the Afghanistan conflict area. The approach used is the System Dynamic method approach. This method is expected to be able to provide scientific contributions in analyzing Indonesia's role in peace in the Afghanistan region so that it becomes the main basis and consideration in making important decisions and policies towards peace in Afghanistan. The results achieved in this study are several analyzes of the role of Indonesia which is very dynamic based on a systemic concept that produces a dynamic causal loop diagram system that reflects the dynamic efforts by Indonesia to participate in maintaining peace in Afghanistan, under the politics of a free and active Indonesian state. Keywords: Indonesia’s Important Role, Peace Afghanistan, System Dynamic Concept Approach.